Association between new onset diabetic retinopathy and monocyte chemoattractant protein-1 (MCP-1) polymorphism in Japanese type 2 diabetes. Issue 3 (June 2015) - Ninomiya, Hiroyo; Katakami, Naoto; Osonoi, Takeshi; Saitou, Miyoko; Yamamoto, Yuichi; Takahara, Mitsuyoshi; Kawamori, Dan; Matsuoka, Taka-aki; Yamasaki, Yoshimitsu; Shimomura, Iichiro
Highlights: MCP-1 plays an important role in the pathogenesis of diabetic retinopathy (DR). A-2518G polymorphism is reported to be associated with the production of MCP-1. We longitudinally examined the association between this polymorphism and onset of DR. The new onset of DR increased with the increase of the number of G alleles. Abstract: We longitudinally evaluated the association between monocyte chemoattractant protein-1 (MCP-1) A-2518G polymorphism and new onset of diabetic retinopathy in 758 type 2 diabetic patients. The new onset of retinopathy increased with the increase of the number of G alleles, even after adjustment for age, HbA1c levels, and duration of diabetes.